Solution to the inverse problem of information security economic management - Левченко, Євген Григорович; Прус, Руслана Богданівна (Ukrainian Information Security Research Journal, 2014)
For finding solution to the inverse problem of economicmanagement parameters of information system must bespecified and required resource amount and optimal resourceallocation between objects must be found. Criterionof optimality is minimization of total loss, which includesloss from information leakage and security costs,or maximization of security investment benefit and itsprofitability. System of two objects is considered; objectsare differed in vulnerability and information quantity.Solution is found in area of saddle point existence, whatprovides reality of findings, since neither of sides interestedin changing their strategy. Fulfilling both conditions –guaranteeing of saddle point state and optimization ofresource allocation – is achieved by controlling of informationsystem parameters: object vulnerabilities and informationdistribution between the objects. The solutionto the inverse problem is the first step to system synthesis.Next step is choosing security mechanisms for eachobject with a glance of their price and threat neutralizingprobabilities.